Analisis Penerimaan Timbangan Balita Berbasis IoT di Kalangan Tenaga Kesehatan Menggunakan Technology Acceptance Model (TAM) - Fidyah Ajeng Wulandari; Wirarama Wedashwara; Heri Wijayanto (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to evaluate the acceptance of IoT-based toddler scales by cadres and health workers at Posyandu by applying the Technology Acceptance Model (TAM). A total of 50 respondents were involved, and the collected data were analyzed using SmartPLS to test the influence of TAM variables on technology acceptance. The analysis revealed that attitude (ATU) was able to explain 63.7% of the variance, indicating that a positive attitude towards technology is a major factor in acceptance. Furthermore, perceived benefits (PU) contributed 57.1%, indicating that respondents adequately recognized the advantages of IoT-based scales. Behavioral intention (BI) also exerts a moderate influence with a contribution of 53.1% of the variance in technology use. However, actual use (AU) only reached 26.5%, indicating a significant gap between intention to use and implementation of the technology in the field due to resistance in the form of concerns related to potential labor reduction. countfor lte to This finding confirms that while the benefits and attitudinal aspects support technology adoption, external factors such as fear of job loss remain barriers to actual implementation.